Factors Affecting Mother's Behavior Towards Complete Basic Immunization in The Working Area of 9 November Health Center Banjarmasin - Laila Rismawati; Anggun Wulandari (Jurnal Berkala Kesehatan, 2023)
Immunization is one of the programs under the health development sector. Based on data of complete basic immunization coverage in South Kalimantan in 2020 is 75.4 percent in 2021 it becomes 80.2 percent, and there is an increase if it was compared to 2020. The purpose of this study is to analyze the relationship between the factors that influence the mother's behavior towards basic immunization. This research is a quantitative study with a cross sectional approach. Sample size using the Slovin formula as much as 93 people. Data analysis in this study using univariate and bivariate with the Chi-square test. Based on the results of this study, there was an influence between income on the mother's behavior toward complete basic immunization because of the p-value <0.05 (0.038). Variabel of education, mother's occupation, father's occupation, number of children, knowledge, and attitude did not affect the completeness of basic immunization in infants because of the p-value >0.05. Income factors are very closely related to health such as immunization in infants. An adequate family income will support the growth and development of children, so parents can provide for all the children's needs, both primary and secondary.